Wypieranie Wody przez Gaz Wtłaczany do Wielowarstwowego Pokładu - Salwa, K.; Walden, H. (Engineering Transactions, 1964)
By solving an equation of the heat conduction type, with appropriate initial and boundary conditions, a function is obtained expressing the pressure distribution in the wet zone of a multi-layer deposit.A transcendental equation is obtained enabling the determination of the displacement of the boundary between the dry and the wet zone. This transcendental equation is solved by means of what is termed a double-tangent approximate method, [2]. Computation has been carried out for a four-layer deposit by means of the UMC-1 computer.